(RE)EXISTÊNCIA DOS PRODUTORES DE ABACAXI EM MONTE ALEGRE DE MINAS (MG) / (RE) EXISTENCE OF PINEAPPLE PRODUCERS IN MONTE ALEGRE DE MINAS (MG) - Alessandra Rodrigues Guimarães; Vera Lúcia Salazar Pessôa (Geo UERJ, 2017)
doi: 10.12957/geouerj.2017.25056